Analysis of Type Cover on Drying Rate and Moisture Content - Anggara, Mietra; Irfan (Publisher Cv. Inara, 2020)
Seaweed is one of the marine commodities that has high economic value and benefits for humans, because seaweed can be processed into basic food ingredients and various types of products such as seaweed lunkhead, gelatin, cosmetic medicines and so on. The post-harvest handling process for the Papuan community, Kec. Taliwang, West Sumbawa Regency (NTB) is still done traditionally so natural drying usually takes a long time because the temperature and energy depend on sunlight. This will lead to a decline in the quality of seaweed products because temperature and energy depend on sunlight. One of the efforts to improve the quality of seaweed production is to reduce the water content, the maximum water content limit, which meets SNI 25% - 50%. In this study, four forms of cover were used, namely the cover form of a single oblique solar dryer, the cover form of the taper solar dryer, the cover form of the double slanted solar dryer, the cover form of the rectangular prism solar dryer. The peak drying rate lies on a double sloping cover of 0.40 g / minute, a taper cover of 0.37 g / minute, a rectangular prism cover of 0.34 g / minute and a single sloping cover of 0.30 g / minute. The hot peaks that are useful are located on a double sloping cover of 3.82 Watt, a taper cover of 2.80 Watt, a rectangular prism cover of 2.09 Watt and a single cover of 0.46 Watt. The peak of efficiency lies in the double sloping cover of 8.57%, taper cover of 6.28%, rectangular prism cover of 4.69% and single sloping cover of 2.28%. The peak of seaweed residual water content lies on a double sloping cover of 13.21%, a taper cover of 19.61%, a rectangular prism cover of 25.73 and a double sloping cover of 27.75%. This shows that drying using double sloping covers is more effective and efficient, so it can accelerate the drying rate and can increase the selling price of seaweed for seaweed farmers in Kertasari Village, Taliwang District, West Sumbawa (NTB).